Pre-Service Teachers' Perception on the Prospective in Teaching English at Schools: Phenomena and Challenges - Fitri, Sundari; Daulay, Sholihatul Hamidah (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Pre-service teachers need to develop skills and apply them as teaching practice in high school to become qualified teachers. Therefore, it is essential to prepare for the availability of a complete and qualified school. The research uses qualitative methods that investigate the challenges faced by teachers based on phenomena occurring in the classroom during teaching practice. The study employed a qualitative phenomenological case study methodology, which helped develop a deeper understanding of the dynamics and complexity of teaching English. In this study, the sampling technician chose three interns as informants who informed the challenges phenomena, and insights that identified cases. This study found that pre-working teachers faced many challenges during the teaching practice in creating an effective classroom, where the influential factors were lack of facilities and insufficient resources. However, this study showed the three challenges that faced the pre-service teacher: lack of respect, and lack of education resources. The findings show that beginner teachers, need to put inductive and productive experiences, not only for teachers but also for school administrators and policymakers to cope with the challenges facing them.